Polyethylene glycol terephthalate protective film and preparation method thereof
Through the cross-linking technology of thiol functional polymer and GMA copolymer, the problem of increased viscosity and residual after high temperature treatment of PET protective film is solved, and the thermal viscosity reduction and residue-free characteristics are achieved. It is suitable for soft and hard bonding lines in the field of electronic packaging Board production.
Patent Information
- Application Number
- CN202411334005.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The existing PET protective film has increased viscosity after high temperature treatment, making it difficult to peel off and retain, affecting the production of soft and hard-to-hard circuit boards in the field of electronic packaging.
The polymer P(OA-co-HEA)-SH, copolymer P(GMA-co-OA) with thiol function, and triethylenetetramine and ethyl acetate are arranged in glue, and the initial cross-linking and high temperature are carried out through low temperature Secondary cross-linking realizes the thermal viscosity reduction and residue-free properties of the PET protective film.
After high temperature treatment at 150-190°C, the PET protective film can be easily peeled off without residues, avoiding the residue of small molecule thiols and irritating odors, reducing production costs, and the synthesis process is simple and easy to industrialize.
Smart Images

Figure CN119144246A_ABST
Abstract
Description
Technical Field The present invention relates to a layered product of a polymer material, in particular to a layered product substantially composed of a synthetic resin, and more particularly to a protective film for a printed circuit board. The present invention also relates to a method for producing the protective film. Background Art Polyethylene terephthalate (PET) has a smooth and shiny surface and excellent properties such as heat resistance and rigidity. It can be used as a protective film substrate and is widely used in the field of electronic packaging. In order to make the PET protective film have special functions (such as antistatic, peelable and / or heat-reducing viscosity, etc.), it is usually necessary to apply a glue coating on its surface (published by Guo Yuying, Wang Hao, Zhang Kuntai, and Shi Qian in "Preparation and Performance Research of Solvent-based Acrylic Pressure-sensitive Adhesive Polyester Surface Protective Film", Liaoning Chemical Industry, 2017, Volume 46, Pages 522-524). Especially in the production process of soft and hard circuit boards in the field of electronic packaging, a large amount of PET protective films with high viscosity before heat treatment are needed, and after high-temperature treatment, the viscosity is reduced to the point that it can be easily peeled off from the copper foil and there is no residue on the copper foil. Adding a layer of glue coating containing a two-component crosslinking agent (component A crosslinking agent and component B crosslinking agent) on the PET base film is a common method for producing high-temperature heat-reduced PET protective film, wherein the component A crosslinking agent can cause the glue to undergo a crosslinking reaction under low temperature conditions, thereby giving the glue coating a sticky characteristic, and the component B crosslinking agent causes the glue to undergo excessive crosslinking and lose its stickiness at high temperatures, thereby enabling the glue coating to have a heat-reduced stickiness function at high temperatures. In the early stage, the applicant tried to use an amine / thiol two-component crosslinking agent, where the amine crosslinking agent causes the glue to undergo a crosslinking reaction at low temperatures, while the thiol causes the glue to undergo excessive crosslinking and lose its stickiness at high temperatures; however, commercially available thiol crosslinking agents are almost all small molecule compounds, and when used as a glue coating for producing PET protective films, small molecule thiols are easily migrated from the glue layer to the surface of the copper foil; after high-temperature treatment, the thiol complexes with the surface of the copper foil, resulting in increased stickiness and inability to separate; at the same time, a large number of thiol molecules remain on the surface of the copper foil, causing adverse effects on subsequent use. Therefore, the research and development of high-temperature heat-resistant and non-residue PET protective film has become a difficulty that needs to be overcome urgently in the field of rigid-flexible circuit board production. Summary of the invention The technical problem to be solved by the present invention is to avoid the deficiencies of the above-mentioned prior art and provide a polyethylene terephthalate protective film and a preparation method thereof. The polyethylene terephthalate protective film prepared by the present invention has high viscosity before heat treatment, and after high-temperature treatment at 150 to 190°C, the viscosity is reduced to the point that it can be easily peeled off from the copper foil of the circuit board without leaving any residue on the copper foil of the circuit board.
[0004] The technical solution adopted by the present invention to solve the technical problem is: Provided is a method for preparing a polyethylene terephthalate protective film, comprising the following steps: Step A: Prepare the thiol-containing polymer P(OA-co-HEA)-SH according to the following steps; A1: Add OA and HEA into a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer, and add ethyl acetate for dilution; A2: Then, weigh a certain amount of AIBN into a glass bottle and dissolve it with ethyl acetate. The evenly dissolved AIBN solution is divided into 5 to 10 portions; A3: Next, the four-necked flask in step A1 is placed in an oil bath, and the temperature of the oil bath is adjusted to 78-95°C. After the mixed solution in the four-necked flask is boiled for 0.5-1 hour, a portion of the AIBN solution in step A2 is added, and a portion of the AIBN solution is added every 1-2 hours until all the portions of the AIBN solution are added, and the reaction is continued for 3-5 hours to obtain a first reaction solution; A4: After the temperature of the first reaction liquid in step A3 drops to room temperature, the first reaction liquid is added to a certain amount of n-hexane for precipitation, filtered to obtain a copolymer of OA and HEA P (OA-co-HEA), and then the copolymer of OA and HEA P (OA-co-HEA) is placed in a vacuum oven at 40 to 60 ° C and dried for 12 to 24 hours; A5: The copolymer P(OA-co-HEA) in step A4 is placed in a round-bottom flask equipped with a water separator, a reflux condenser and a magnetic stirring device, and xylene is added to the round-bottom flask to completely dissolve the copolymer P(OA-co-HEA); thioglycolic acid and p-toluenesulfonic acid are then added, and the solution in the round-bottom flask is heated to boil, and stirred for reaction for 2 to 5 hours to obtain a second reaction solution; A6: After the temperature of the second reaction liquid in step A5 drops to room temperature, a certain amount of n-hexane is added for precipitation, and after filtration, a polymer containing thiol groups P(OA-co-HEA)-SH is obtained, which is placed in a vacuum oven at 40-60°C and dried for 12-24 hours; Step B: Prepare the copolymer P (GMA-co-OA) of GMA and OA according to the following steps; B1: Add GMA and OA into a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer, and add ethyl acetate for dilution; B2: Then, weigh a certain amount of AIBN into a glass bottle and dissolve it with ethyl acetate. The evenly dissolved AIBN solution is divided into 5 to 10 portions; B3: Next, the four-necked flask in step B1 is placed in an oil bath, and the temperature of the oil bath is adjusted to 78-95° C. After the mixed solution in the four-necked flask is boiled for 0.5-1 hour, a portion of the AIBN solution in step B2 is added, and a portion of the AIBN solution is added every 1-2 hours until all portions of the AIBN solution are added, and the reaction is continued for 3-5 hours to obtain a third reaction solution; B4: After the temperature of the third reaction liquid in step B3 drops to room temperature, the third reaction liquid is added to a certain amount of n-hexane to obtain a copolymer of GMA and OA P (GMA-co-OA), and the copolymer is placed in a vacuum oven at 40 to 60 °C and dried for 12 to 24 hours; Step C: preparing glue with a certain amount of the thiol-containing polymer P(OA-co-HEA)-SH prepared in step A, a certain amount of the copolymer of GMA and OA P(GMA-co-OA) prepared in step B, a certain amount of triethylenetetramine and a certain amount of ethyl acetate, applying the glue to any surface of PET, drying, and cooling to obtain a polyethylene terephthalate protective film; The step A and step B are in no particular order.
[0005] In step A1, the mass ratio of HEA to OA is 1:(3-10), and the mass ratio of the total mass of monomers OA and HEA to ethyl acetate is 1:(2-5); In step A4, when precipitating P(OA-co-HEA), the volume ratio of the first reaction solution to n-hexane is 1:(3-10); In step A5, the mass ratio of P(OA-co-HEA) to thioglycolic acid is 1:(0.5-1), the mass ratio of P(OA-co-HEA) to xylene is 1:(5-10), and the mass ratio of p-toluenesulfonic acid to thioglycolic acid is 1:(50-100); In step A6, when precipitating P(OA-co-HEA)-SH, the volume ratio of the second reaction solution to n-hexane is 1: (3-10).
[0006] In step A5, the heating temperature is 140 to 150°C.
[0007] In step B1, the mass ratio of GMA to OA is 1:(2-5), and the mass ratio of the total mass of GMA and OA to ethyl acetate is 1:(2-5); In step B4, the volume ratio of the third reaction liquid to n-hexane is 1:(3-10).
[0008] In step C, the mass ratio of triethylenetetramine, the thiol-containing polymer P(OA-co-HEA)-SH and the copolymer of GMA and OA P(GMA-co-OA) is (0.1-1.5):(0.5-2):(10-100); the ratio of the total mass of triethylenetetramine, P(OA-co-HEA)-SH and P(GMA-co-OA) to ethyl acetate is 1:(2-5).
[0009] In step C, the temperature during drying is 50-80°C.
[0010] The present invention also provides a polyethylene terephthalate protective film, which is obtained according to the preparation method of the polyethylene terephthalate protective film. Specifically, the polyethylene terephthalate protective film comprises a PET base film layer and a glue layer coated on any surface of the PET base film layer, and the glue layer comprises a thiol-containing polymer P(OA-co-HEA)-SH, a copolymer of GMA and OA P(GMA-co-OA), triethylenetetramine and ethyl acetate; wherein the thiol-containing polymer P(OA-co-HEA)-SH mainly comprises a copolymer of OA and HEA P(OA-co-HEA), xylene, thioglycolic acid and p-toluenesulfonic acid, and the copolymer of OA and HEA P(OA-co-HEA) mainly comprises OA and HEA; and the copolymer of GMA and OA P(GMA-co-OA) mainly comprises GMA and OA.
[0011] Compared with the prior art, the polyethylene terephthalate protective film and the preparation method thereof of the present invention have the following beneficial effects: The invention uses azobisisobutyronitrile (AIBN) to initiate polymerization of n-octyl acrylate (OA) and hydroxyethyl acrylate (HEA) in ethyl acetate to prepare a copolymer P(OA-co-HEA) of n-octyl acrylate and hydroxyethyl acrylate; then, under the catalytic action of p-toluenesulfonic acid, P(OA-co-HEA) and thioglycolic acid are refluxed in xylene to prepare a polymer P(OA-co-HEA)-SH with a thiol group; then, AIBN is used to initiate polymerization of glycidyl methacrylate (GMA) and n-octyl acrylate (OA) in ethyl acetate to prepare a polymer P(GMA-co-OA) of glycidyl methacrylate and n-octyl acrylate; finally, glue is prepared by using P(GMA-co-OA), triethylenetetramine, P(OA-co-HEA)-SH and ethyl acetate, and the glue is applied on any surface of PET to obtain a polyethylene terephthalate (PET) protective film with thermal viscosity reduction.
[0012] In the preparation method of the present invention, the amine crosslinking agent (such as triethylenetetramine) and the epoxy polymer can undergo a primary crosslinking reaction in a low temperature environment of 10 to 40°C, so that the adhesive layer of the PET protective film has a higher adhesive property; when the temperature is raised to above 150°C, for example, in an environment of 150 to 190°C, the mercapto group and the epoxy polymer undergo a secondary crosslinking reaction, so that the adhesive layer of the PET protective film is over-crosslinked and loses its adhesive property, thereby being completely separated from the protected object, that is, the protective film of the present invention is reduced in viscosity after high temperature treatment of 150 to 190°C to the point that it can be easily peeled off from the copper foil of the circuit board; in addition, a synthesized polymer with multiple mercapto groups is used as a secondary crosslinking agent, that is, P(OA-co-HEA)-SH is used as a secondary crosslinking agent , avoiding the pungent smell of small molecule thiol, the polymer is non-volatile and has no odor, and is entangled with the polymer chain in the glue solution, and will not remain on the surface of the protected object, that is, the protective film of the present invention has no residue on the copper foil of the circuit board and does not pollute the protected material; therefore, the polyethylene terephthalate protective film of the present invention has no pungent smell, and can be separated from the copper foil of the circuit board after high-temperature treatment without residue; the synthesis method is simple and convenient, and is easy to scale up for industrial production, and when the polyethylene terephthalate protective film of the present invention is prepared, the synthesis process does not require special equipment, and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a schematic diagram represented by chemical molecular formula in the preparation process of polyethylene terephthalate protective film of the present invention; Figure 2 1 is a schematic diagram of the gel permeation chromatography test results of the copolymer of OA and HEA P (OA-co-HEA) in Example 1 of the method for preparing a polyethylene terephthalate protective film of the present invention; it can be seen from the figure that the number average molecular weight of the copolymer of OA and HEA P (OA-co-HEA) is 1.036×10 6 , the molecular weight distribution is 3.91, indicating that a high molecular weight polymer was successfully synthesized; Figure 3 Schematic diagram of infrared test results of the copolymer of OA and HEA P(OA-co-HEA) and the polymer P(OA-co-HEA)-SH containing a thiol group in Example 1; it can be seen from the figure that the polymer P(OA-co-HEA)-SH containing a thiol group has a wavelength of 2575 cm -1 The vibration absorption peak of the thiol group appeared. The signal was weak because the vibration absorption peak of the thiol group itself was weak in the infrared spectrum and had nothing to do with the content of the thiol group. This proved that thioglycolic acid successfully reacted with the copolymer P(OA-co-HEA) to generate the polymer P(OA-co-HEA)-SH containing thiol groups. Figure 4Schematic diagram of the gel permeation chromatography test results of the copolymer of GMA and OA P (GMA-co-OA) in Example 1; it can be seen from the figure that the number average molecular weight of the copolymer of GMA and OA P (GMA-co-OA) is 0.991×10 6 , the molecular weight distribution is 4.03, indicating that a high molecular weight polymer was successfully synthesized; Figure 5 This is a table showing the properties of various embodiments of the method for preparing a polyethylene terephthalate protective film of the present invention. DETAILED DESCRIPTION
[0014] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0015] In the present invention, OA is the English abbreviation of n-octyl acrylate, HEA is the English abbreviation of hydroxyethyl acrylate, AIBN is the English abbreviation of azobisisobutyronitrile, and GMA is the English abbreviation of glycidyl methacrylate.
[0016] A method for preparing a polyethylene terephthalate protective film comprises the following steps: Step A: Prepare the thiol-containing polymer P(OA-co-HEA)-SH according to the following steps; A1: OA and HEA are added to a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer, and ethyl acetate is added for dilution; in this step A1, the mass ratio of HEA to OA is 1:(3-10), and the mass ratio of the total mass of monomers OA and HEA to ethyl acetate is 1:(2-5); A2: Then, a certain amount of AIBN is weighed into a glass bottle and dissolved with ethyl acetate, and the evenly dissolved AIBN solution is evenly divided into 5 to 10 portions; in this step A2, the mass ratio of the total mass of the monomers OA and HEA to AIBN is 1:(0.002 to 0.02), and the mass ratio of AIBN to ethyl acetate is 1:(50 to 200); A3: Next, the four-necked flask in step A1 is placed in an oil bath, and the temperature of the oil bath is adjusted to 78-95° C. After the mixed solution in the four-necked flask is boiled for 0.5-1 hour, a portion of the AIBN solution in step A2 is added, and a portion of the AIBN solution is added every 1-2 hours until all the portions of the AIBN solution are added, and the reaction is continued for 3-5 hours to obtain a first reaction solution; A4: After the temperature of the first reaction liquid in step A3 drops to room temperature, the first reaction liquid is added to a certain amount of n-hexane for precipitation, filtered to obtain a copolymer of OA and HEA P(OA-co-HEA), and then the copolymer of OA and HEA P(OA-co-HEA) is placed in a vacuum oven at 40 to 60° C. and dried for 12 to 24 hours; in step A4, when precipitating P(OA-co-HEA), the volume ratio of the first reaction liquid to n-hexane is 1:(3 to 10); A5: The copolymer P(OA-co-HEA) in step A4 is placed in a round-bottom flask equipped with a water separator, a reflux condenser and a magnetic stirring device, and xylene is added to the round-bottom flask to completely dissolve the copolymer P(OA-co-HEA); thioglycolic acid and p-toluenesulfonic acid are then added, and the solution in the round-bottom flask is heated to boil, and the temperature during heating can be controlled to be 140-150° C., and the reaction is stirred for 2-5 hours to obtain a second reaction solution; in step A5, the mass ratio of P(OA-co-HEA) to thioglycolic acid is 1:(0.5-1), the mass ratio of P(OA-co-HEA) to xylene is 1:(5-10), and the mass ratio of p-toluenesulfonic acid to thioglycolic acid is 1:(50-100); A6: After the temperature of the second reaction liquid in step A5 drops to room temperature, a certain amount of n-hexane is added for precipitation, and after filtering, a polymer P(OA-co-HEA)-SH containing a thiol group is obtained, and the polymer is placed in a vacuum oven at 40 to 60° C. and dried for 12 to 24 hours; in step A6, when precipitating P(OA-co-HEA)-SH, the volume ratio of the second reaction liquid to n-hexane is 1:(3 to 10); Step B: Prepare the copolymer P (GMA-co-OA) of GMA and OA according to the following steps; B1: GMA and OA are added to a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer, and ethyl acetate is added for dilution; in this step B1, the mass ratio of GMA to OA is 1: (2-5), and the mass ratio of the total mass of GMA and OA to ethyl acetate is 1: (2-5); B2: Then, a certain amount of AIBN is weighed into a glass bottle and dissolved with ethyl acetate, and the evenly dissolved AIBN solution is evenly divided into 5 to 10 portions; in this step B2, the mass ratio of the total mass of GMA and OA to AIBN is 1:(0.002 to 0.02), and the mass ratio of AIBN to ethyl acetate is 1:(50 to 200); B3: Next, the four-necked flask in step B1 is placed in an oil bath, and the temperature of the oil bath is adjusted to 78-95° C. After the mixed solution in the four-necked flask is boiled for 0.5-1 hour, a portion of the AIBN solution in step B2 is added, and a portion of the AIBN solution is added every 1-2 hours until all portions of the AIBN solution are added, and the reaction is continued for 3-5 hours to obtain a third reaction solution; B4: After the temperature of the third reaction liquid in step B3 drops to room temperature, the third reaction liquid is added to a certain amount of n-hexane to obtain a copolymer of GMA and OA P (GMA-co-OA), and the copolymer is placed in a vacuum oven at 40 to 60 °C and dried for 12 to 24 hours; in step B4, the volume ratio of the third reaction liquid to n-hexane is 1:(3 to 10); Step C: prepare glue with a certain amount of the thiol-containing polymer P(OA-co-HEA)-SH prepared in step A, a certain amount of the copolymer of GMA and OA P(GMA-co-OA) prepared in step B, a certain amount of triethylenetetramine and a certain amount of ethyl acetate, apply it on any surface of PET, dry it, and the temperature during drying can be controlled to be 50-80° C. After cooling, a polyethylene terephthalate protective film is obtained; in step C, the mass ratio of the triethylenetetramine, the thiol-containing polymer P(OA-co-HEA)-SH and the copolymer of GMA and OA P(GMA-co-OA) is (0.1-1.5):(0.5-2):(10-100); the ratio of the total mass of triethylenetetramine, P(OA-co-HEA)-SH and P(GMA-co-OA) to ethyl acetate is 1:(2-5); The step A and step B are in no particular order.
[0017] The present invention also provides a polyethylene terephthalate protective film obtained by the above-mentioned method for preparing the polyethylene terephthalate protective film, which is used in the field of soft-hard combined circuit board production. Specifically, the polyethylene terephthalate protective film of the present invention comprises a PET base film layer and a glue layer coated on any surface of the PET base film layer, and the glue layer comprises a thiol-containing polymer P(OA-co-HEA)-SH, a copolymer of GMA and OA P(GMA-co-OA), triethylenetetramine and ethyl acetate; wherein the thiol-containing polymer P(OA-co-HEA)-SH mainly comprises a copolymer of OA and HEA P(OA-co-HEA), xylene, thioglycolic acid and p-toluenesulfonic acid, and the copolymer of OA and HEA P(OA-co-HEA) further comprises OA, HEA, AIBN and ethyl acetate; the copolymer of GMA and OA P(GMA-co-OA) comprises GMA, OA, AIBN and ethyl acetate. Example
[0018] A method for preparing a polyethylene terephthalate protective film comprises the following steps: Step A: Prepare the thiol-containing polymer P(OA-co-HEA)-SH according to the following steps; A1: 60 g of OA and 20 g of HEA were added to a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer. The capacity of the four-necked flask was 1 liter. 240 g of ethyl acetate was added for dilution. The stirring device used a mechanical stirring device. A2: Then, weigh 0.4 g of AIBN into a glass bottle and dilute it to 30 g with ethyl acetate. The evenly dissolved AIBN solution is divided into 6 portions, each of which is 5 g. A3: Next, the four-necked flask in step A1 is placed in an oil bath, the oil bath temperature is adjusted to 90°C, and the speed of the mechanical stirring device is 130 rpm. After the mixed solution in the four-necked flask is boiled for 0.5 hours, a portion of the AIBN solution in step A2 is added. The AIBN solution is an initiator. A portion of the AIBN solution is added every hour until all the portions of the AIBN solution are added. The reaction is continued for 3 hours to obtain a first reaction solution. A4: After the temperature of the first reaction liquid in step A3 drops to room temperature, the first reaction liquid is added to 1.2 kg of n-hexane for precipitation, and filtered to obtain a copolymer of OA and HEA P (OA-co-HEA), and then the copolymer of OA and HEA P (OA-co-HEA) is placed in a vacuum oven at 50° C. and dried for 15 hours; A5: 50 g of the copolymer P(OA-co-HEA) prepared in step A4 was placed in a round-bottom flask equipped with a water separator, a reflux condenser and a magnetic stirring device, 300 g of xylene was added to the round-bottom flask, and the copolymer P(OA-co-HEA) was completely dissolved by stirring; 30 g of thioglycolic acid and 0.3 g of p-toluenesulfonic acid were then added, and the solution in the round-bottom flask was heated to boil. The temperature during heating can be controlled to be 145° C., and the mixture was stirred for reaction for 3 hours to obtain a second reaction solution; A6: After the temperature of the second reaction liquid in step A5 drops to room temperature, 1.8 kg of n-hexane is added for precipitation. After filtration, a thiol-containing polymer P(OA-co-HEA)-SH is obtained, which is placed in a vacuum oven at 50°C and dried for 24 hours; See also Figure 2 The GPC (gel permeation chromatography) test results show that the number average molecular weight of the copolymer of OA and HEA P(OA-co-HEA) of Example 1 is 1.036×10 6 , the molecular weight distribution is 3.91, indicating that a high molecular weight polymer was successfully synthesized; see Figure 3The infrared detection results show that the polymer P(OA-co-HEA)-SH containing thiol groups in Example 1 has a wavelength of 2575 cm -1 The vibration absorption peak of the thiol group appeared. The signal was weak because the vibration absorption peak of the thiol group itself was weak in the infrared spectrum and had nothing to do with the content of the thiol group. This proved that thioglycolic acid successfully reacted with the copolymer P(OA-co-HEA) to generate the polymer P(OA-co-HEA)-SH containing thiol groups. Step B: Prepare the copolymer P (GMA-co-OA) of GMA and OA according to the following steps; B1: 20 g of GMA and 40 g of OA were added to a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer, and 180 g of ethyl acetate was added for dilution. The stirring device used a mechanical stirring device; B2: Then, weigh 0.3 g of AIBN into a clean glass bottle and dilute it to 30 g with ethyl acetate. The evenly dissolved AIBN solution is divided into 6 portions, each of which is 5 g. B3: Next, the four-necked flask in step B1 is placed in an oil bath, and the temperature of the oil bath is adjusted to 90° C. After the mixed solution in the four-necked flask is boiled for 0.5 hour, a portion of the AIBN solution in step B2 is added, and a portion of the AIBN solution is added every 1 hour until all the portions of the AIBN solution are added, and the reaction is continued for 3 hours to obtain a third reaction solution; B4: After the temperature of the third reaction liquid in step B3 drops to room temperature, the third reaction liquid is added dropwise into 900 g of n-hexane to obtain a copolymer of GMA and OA P (GMA-co-OA), which is then placed in a vacuum oven at 50° C. and dried for 24 hours; See also Figure 4 The GPC (gel permeation chromatography) test results show that the number average molecular weight of the copolymer of GMA and OA P (GMA-co-OA) of this embodiment 1 is 0.991×10 6 , the molecular weight distribution is 4.03, indicating that a high molecular weight polymer was successfully synthesized; Step C: Weigh 0.25 g of triethylenetetramine, take 0.5 g of a thiol-containing polymer P(OA-co-HEA)-SH, 100 g of a copolymer of GMA and OA P(GMA-co-OA) and 300 g of ethyl acetate to prepare a glue, apply it to any surface of 25 μm PET at a thickness of 25 μm, dry it, and the temperature during drying can be controlled to be 50° C. After cooling, a thermally de-viscous polyethylene terephthalate protective film is obtained; In this embodiment, step A and step B are performed in no particular order. Example
[0019] The method is basically the same as Example 1, except that the amount of the thiol-containing polymer P(OA-co-HEA)-SH in Step C is different. The thiol-containing polymer P(OA-co-HEA)-SH in Example 2 is 1.0 g. Example
[0020] The method is basically the same as Example 1, except that the amount of the thiol-containing polymer P(OA-co-HEA)-SH in Step C is different. The thiol-containing polymer P(OA-co-HEA)-SH in Example 3 is 2.0 g. Example
[0021] The method is basically the same as Example 1, except that the amount of some substances in step A is slightly different, specifically: Step A1: OA is 100 g, ethyl acetate is 360 g; Step A2: 0.6 g of AIBN; Step A4: 1.8 kg of n-hexane; Therefore, the GPC (gel permeation chromatography) test results of Example 4 show that the number average molecular weight of the copolymer of OA and HEA P(OA-co-HEA) of Example 4 is 0.994×10 6 , the molecular weight distribution is 3.76, indicating that a high molecular weight polymer was successfully synthesized; the infrared detection results show that the thiol-containing polymer P(OA-co-HEA)-SH of Example 4 has a wave number of 2576 cm -1 The vibration absorption peak of mercapto group appeared. Example
[0022] It is basically the same as Example 4, except that the amount of the thiol-containing polymer P(OA-co-HEA)-SH in Step C is different. The thiol-containing polymer P(OA-co-HEA)-SH in this Example 5 is 1.0 g. Example
[0023] It is basically the same as Example 4, except that the amount of the thiol-containing polymer P(OA-co-HEA)-SH in Step C is different. The thiol-containing polymer P(OA-co-HEA)-SH in this Example 6 is 2.0 g. Example
[0024] The method is basically the same as Example 1, except that the amount of some substances in step A is slightly different, specifically: Step A1: OA is 200 g, ethyl acetate is 660 g, and the capacity of the four-necked flask is 2 liters; Step A2: 1.1 g of AIBN; Step A4: 3.3 kg of n-hexane; Therefore, the GPC (gel permeation chromatography) test results of Example 4 show that the number average molecular weight of the copolymer of OA and HEA P(OA-co-HEA) of Example 4 is 0.986×10 6 The molecular weight distribution is 3.81, indicating that a high molecular weight polymer was successfully synthesized. The infrared detection results show that the polymer P(OA-co-HEA)-SH containing thiol groups in Example 4 has a wavelength of 2577 cm -1 The vibration absorption peak of mercapto group appeared. Example
[0025] It is basically the same as Example 7, except that the amount of the thiol-containing polymer P(OA-co-HEA)-SH in Step C is different. The thiol-containing polymer P(OA-co-HEA)-SH in this Example 8 is 1.0 g. Example
[0026] It is basically the same as Example 7, except that the amount of the thiol-containing polymer P(OA-co-HEA)-SH in Step C is different. The thiol-containing polymer P(OA-co-HEA)-SH in this Example 9 is 2.0 g. Example
[0027] The method is basically the same as Example 4, except that the amount of some substances in steps B and C is slightly different, specifically: Step B1: OA is 60 g, ethyl acetate is 240 g; Step B2: AIBN: 0.4 g; Step B4: 1.2 kg of n-hexane; Therefore, the GPC (gel permeation chromatography) test results of Example 10 show that the number average molecular weight of the copolymer of GMA and OA P (GMA-co-OA) of Example 10 is 0.916×10 6 , the molecular weight distribution is 3.94, indicating that a high molecular weight polymer was successfully synthesized; Step C: The amount of the thiol-containing polymer P(OA-co-HEA)-SH was 1.0 g. Example
[0028] The method is basically the same as Example 10, except that the amount of some substances in step B is slightly different, specifically: Step B1: OA is 80 g, ethyl acetate is 300 g; Step B2: AIBN: 0.5 g; Step B4: 1.8 kg of n-hexane; Therefore, the GPC (gel permeation chromatography) test results of this Example 11 show that the number average molecular weight of the copolymer of GMA and OA P (GMA-co-OA) of this Example 11 is 0.885×10 6 , the molecular weight distribution is 3.83, indicating that a high molecular weight polymer was successfully synthesized. Example
[0029] The method is basically the same as Example 10, except that the amount of some substances in step B is slightly different, specifically: Step B1: OA is 100 g, ethyl acetate is 360 g; Step B2: AIBN: 0.6 g; Step B4: 1.8 kg of n-hexane; Therefore, the GPC (gel permeation chromatography) test results of Example 12 show that the number average molecular weight of the copolymer of GMA and OA P (GMA-co-OA) of Example 12 is 0.876×10 6 , the molecular weight distribution is 3.88, indicating that a high molecular weight polymer was successfully synthesized.
[0030] Figure 5 This is a table comparing the properties of various embodiments of the method for preparing a polyethylene terephthalate protective film of the present invention with a PET protective film prepared without P(OA-co-HEA)-SH and a PET protective film prepared with pentaerythritol thioglycolate. The heat treatment of the peeling force (gf / 25 mm) after heat treatment in the table refers to: treating each sample at a temperature of 180°C for 1 hour. The PET protective film prepared without P(OA-co-HEA)-SH refers to: glue formula: 0.25 grams of triethylenetetramine, 100 grams of P(GMA-co-OA) and 300 grams of ethyl acetate, according to a 25 μm (micrometer) thick glue coating on a 25 μm (micrometer) thick PET surface, and a PET protective film formed after drying at 50°C, P(GMA-co-OA) uses the P(GMA-co-OA) prepared in Example 1. The PET protective film prepared by using pentaerythritol thioglycolate refers to: glue formula: 0.25 grams of triethylenetetramine, 1.0 grams of pentaerythritol thioglycolate, 100 grams of P(GMA-co-OA) and 300 grams of ethyl acetate, according to the glue with a thickness of 25 μm (micrometer) applied to the PET surface with a thickness of 25 μm (micrometer), and the PET protective film formed after drying at 50°C, P(GMA-co-OA) uses the P(GMA-co-OA) prepared in Example 1. Gf is gram-force, which is a unit of force, indicating the gravity of a substance with a mass of 1 gram, and gf / 25 mm is the peeling force of the protective film with a unit width of 25 mm.
[0031] from Figure 5 As can be seen from the table, the peeling forces of Examples 1 to 12 of the present invention and the PET protective film prepared without using P(OA-co-HEA)-SH are basically the same at room temperature, among which Examples 1 to 9 are slightly smaller, and Examples 10 to 12 are slightly larger; however, the peeling forces after heat treatment of Examples 1 to 12 of the present invention are much smaller than that of the PET protective film prepared without using P(OA-co-HEA)-SH, and the viscosity of Examples 1 to 12 of the present invention before heat treatment (for example, room temperature) is reduced compared with that after treatment at high temperatures of 150 to 190°C (for example, temperature 180°C). The peeling force 435 (gf / 25 mm) of the PET protective film prepared without P(OA-co-HEA)-SH after heat treatment is much greater than the peeling force 193 (gf / 25 mm) at room temperature. This indicates that although the PET protective film prepared without P(OA-co-HEA)-SH also has high viscosity before heat treatment (for example, at room temperature), the viscosity is enhanced after treatment at a high temperature of 150 to 190 °C (for example, a temperature of 180 °C), making it difficult to peel off from the copper foil of the circuit board after treatment at a high temperature of 150 to 190 °C (for example, a temperature of 180 °C).
[0032] The peeling force 23 (gf / 25 mm) of the polyethylene terephthalate protective film prepared in Example 1 of the present invention after heat treatment is much smaller than the peeling force 146 (gf / 25 mm) at room temperature. The peeling force 8 (gf / 25 mm) of the polyethylene terephthalate protective film prepared in Example 2 of the present invention after heat treatment is much smaller than the peeling force 144 (gf / 25 mm) at room temperature. The peeling force 3 (gf / 25 mm) of the polyethylene terephthalate protective film prepared in Example 3 of the present invention after heat treatment is much smaller than the peeling force 131 (gf / 25 mm) at room temperature. The peeling force 47 (gf / 25 mm) of the polyethylene terephthalate protective film prepared in Example 4 of the present invention after heat treatment is much smaller than the peeling force 159 (gf / 25 mm) at room temperature. The peeling force 28 (gf / 25 mm) of the polyethylene terephthalate protective film prepared in Example 5 of the present invention after heat treatment is much smaller than the peeling force 160 (gf / 25 mm) at room temperature. The peeling force of the polyethylene terephthalate protective film prepared in Example 6 of the present invention after heat treatment is 12 (gf / 25 mm) which is much smaller than the peeling force of 147 (gf / 25 mm) at room temperature. The peeling force of the polyethylene terephthalate protective film prepared in Example 7 of the present invention after heat treatment is 95 (gf / 25 mm) which is much smaller than the peeling force of 187 (gf / 25 mm) at room temperature. The peeling force of the polyethylene terephthalate protective film prepared in Example 8 of the present invention after heat treatment is 78 (gf / 25 mm) which is much smaller than the peeling force of 179 (gf / 25 mm) at room temperature. The peeling force of the polyethylene terephthalate protective film prepared in Example 9 of the present invention after heat treatment is 54 (gf / 25 mm) which is much smaller than the peeling force of 161 (gf / 25 mm) at room temperature. The peeling force of the polyethylene terephthalate protective film prepared in Example 10 of the present invention after heat treatment is 35 (gf / 25 mm) much smaller than the peeling force 213 (gf / 25 mm) at room temperature. The peeling force of the polyethylene terephthalate protective film prepared in Example 11 of the present invention after heat treatment is 92 (gf / 25 mm) much smaller than the peeling force 253 (gf / 25 mm) at room temperature. The peeling force of the polyethylene terephthalate protective film prepared in Example 12 of the present invention after heat treatment is 173 (gf / 25 mm) much smaller than the peeling force 332 (gf / 25 mm) at room temperature. mm) is also much smaller; it can be seen from Example 1 to Example 12 that the polyethylene terephthalate protective film prepared by the present invention also has a high viscosity before heat treatment (for example, at room temperature), and the viscosity is reduced after treatment at a high temperature of 150 to 190°C (for example, a temperature of 180°C), and the viscosity is reduced to the point that it can be easily peeled off from the copper foil of the circuit board, and no residue is left on the copper foil of the circuit board.
[0033] from Figure 5As can be seen from the table, compared with the PET protective film prepared using pentaerythritol thioglycolate, the peeling forces of Examples 1 to 12 of the present invention at room temperature are basically the same, and Examples 1 to 12 are slightly larger; however, the peeling forces of Examples 1 to 12 of the present invention after heat treatment are much smaller than that of the PET protective film prepared using pentaerythritol thioglycolate, and the viscosity of Examples 1 to 12 of the present invention before heat treatment (for example, at room temperature) is reduced compared with that after treatment at high temperatures of 150 to 190°C (for example, at 180°C). The peeling force 1253 (gf / 25 mm) of the PET protective film prepared with pentaerythritol thioglycolate after heat treatment is much greater than the peeling force 127 (gf / 25 mm) at room temperature. This shows that although the PET protective film prepared with pentaerythritol thioglycolate also has high viscosity before heat treatment (for example, at room temperature), the viscosity is greatly enhanced after treatment at a high temperature of 150-190°C (for example, a temperature of 180°C), making it very difficult to peel off the copper foil of the circuit board after treatment at a high temperature of 150-190°C (for example, a temperature of 180°C), and there are residues on the copper foil of the circuit board.
[0034] The equipment used in the embodiments of the present invention is as follows: Infrared spectrometer (IR): Nicolet 6700 infrared spectrometer produced by Thermofisher (Thermo Fisher Scientific).
[0035] Gel permeation chromatography: mobile phase is DMF, two Agilent columns (Polar Gel-M and PolarGel-L), eluent flow rate is 1.0 mL / min, column temperature is 50°C, column standard curve is calibrated with polymethyl methacrylate, relative molecular weight (M) is determined n ).
[0036] Digital display electronic universal testing machine: The digital display electronic universal testing machine model STS100KN produced by Xiamen Easy Instrument Co., Ltd.
[0037] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the scope covered by the claims of the present invention.
Claims
1. A method for preparing a polyethylene terephthalate protective film, characterized in that: The following steps are involved: Step A: Prepare the thiol-containing polymer P(OA-co-HEA)-SH according to the following steps; A1: Add OA and HEA into a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer, and add ethyl acetate for dilution; A2: Then, weigh a certain amount of AIBN into a glass bottle and dissolve it with ethyl acetate. The evenly dissolved AIBN solution is divided into 5 to 10 portions; A3: Next, the four-necked flask in step A1 is placed in an oil bath, and the temperature of the oil bath is adjusted to 78-95°C. After the mixed solution in the four-necked flask is boiled for 0.5-1 hour, a portion of the AIBN solution in step A2 is added, and a portion of the AIBN solution is added every 1-2 hours until all the portions of the AIBN solution are added, and the reaction is continued for 3-5 hours to obtain a first reaction solution; A4: After the temperature of the first reaction liquid in step A3 drops to room temperature, the first reaction liquid is added to a certain amount of n-hexane for precipitation, filtered to obtain a copolymer of OA and HEA P (OA-co-HEA), and then the copolymer of OA and HEA P (OA-co-HEA) is placed in a vacuum oven at 40 to 60 ° C and dried for 12 to 24 hours; A5: The copolymer P(OA-co-HEA) in step A4 is placed in a round-bottom flask equipped with a water separator, a reflux condenser and a magnetic stirring device, and xylene is added to the round-bottom flask to completely dissolve the copolymer P(OA-co-HEA); thioglycolic acid and p-toluenesulfonic acid are then added, and the solution in the round-bottom flask is heated to boil, and stirred for reaction for 2 to 5 hours to obtain a second reaction solution; A6: After the temperature of the second reaction liquid in step A5 drops to room temperature, a certain amount of n-hexane is added for precipitation, and after filtration, a polymer containing thiol groups P(OA-co-HEA)-SH is obtained, which is placed in a vacuum oven at 40-60°C and dried for 12-24 hours; Step B: Prepare the copolymer P (GMA-co-OA) of GMA and OA according to the following steps; B1: Add GMA and OA into a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a stirring device and a thermometer, and add ethyl acetate for dilution; B2: Then, weigh a certain amount of AIBN into a glass bottle and dissolve it with ethyl acetate. The evenly dissolved AIBN solution is divided into 5 to 10 portions; B3: Next, the four-necked flask in step B1 is placed in an oil bath, and the temperature of the oil bath is adjusted to 78-95° C. After the mixed solution in the four-necked flask is boiled for 0.5-1 hour, a portion of the AIBN solution in step B2 is added, and a portion of the AIBN solution is added every 1-2 hours until all portions of the AIBN solution are added, and the reaction is continued for 3-5 hours to obtain a third reaction solution; B4: After the temperature of the third reaction liquid in step B3 drops to room temperature, the third reaction liquid is added to a certain amount of n-hexane to obtain a copolymer of GMA and OA P (GMA-co-OA), and the copolymer is placed in a vacuum oven at 40 to 60 °C and dried for 12 to 24 hours; Step C: preparing glue with a certain amount of the thiol-containing polymer P(OA-co-HEA)-SH prepared in step A, a certain amount of the copolymer of GMA and OA P(GMA-co-OA) prepared in step B, a certain amount of triethylenetetramine and a certain amount of ethyl acetate, applying the glue to any surface of PET, drying, and cooling to obtain a polyethylene terephthalate protective film; The step A and step B are in no particular order.
2. The method for preparing a polyethylene terephthalate protective film according to claim 1, characterized in that: In step A1, the mass ratio of HEA to OA is 1:(3-10), and the mass ratio of the total mass of monomers OA and HEA to ethyl acetate is 1:(2-5); In step A4, when precipitating P(OA-co-HEA), the volume ratio of the first reaction solution to n-hexane is 1:(3-10); In step A5, the mass ratio of P(OA-co-HEA) to thioglycolic acid is 1:(0.5-1), the mass ratio of P(OA-co-HEA) to xylene is 1:(5-10), and the mass ratio of p-toluenesulfonic acid to thioglycolic acid is 1:(50-100); In step A6, when precipitating P(OA-co-HEA)-SH, the volume ratio of the second reaction solution to n-hexane is 1: (3-10).
3. The method for preparing a polyethylene terephthalate protective film according to claim 1, characterized in that: In step A5, the temperature during heating is 140 to 150°C.
4. The method for preparing a polyethylene terephthalate protective film according to claim 1, characterized in that: In step B1, the mass ratio of GMA to OA is 1:(2-5), and the mass ratio of the total mass of GMA and OA to ethyl acetate is 1:(2-5); In step B4, the volume ratio of the third reaction liquid to n-hexane is 1:(3-10).
5. The method for preparing a polyethylene terephthalate protective film according to claim 1, characterized in that: In step C, the mass ratio of triethylenetetramine, the thiol-containing polymer P(OA-co-HEA)-SH and the copolymer of GMA and OA P(GMA-co-OA) is (0.1-1.5):(0.5-2):(10-100); the ratio of the total mass of triethylenetetramine, P(OA-co-HEA)-SH and P(GMA-co-OA) to ethyl acetate is 1:(2-5).
6. The method for preparing a polyethylene terephthalate protective film according to claim 1, characterized in that: In step C, the temperature during drying is 50-80°C.
7. A polyethylene terephthalate protective film, characterized in that: The polyethylene terephthalate protective film obtained by the preparation method of the polyethylene terephthalate protective film according to any one of claims 1 to 6, specifically, the polyethylene terephthalate protective film comprises a PET base film layer and a glue layer coated on any surface of the PET base film layer, the glue layer comprises a thiol-containing polymer P(OA-co-HEA)-SH, a copolymer of GMA and OA P(GMA-co-OA), triethylenetetramine and ethyl acetate; wherein the thiol-containing polymer P(OA-co-HEA)-SH mainly comprises a copolymer of OA and HEA P(OA-co-HEA), xylene, thioglycolic acid and p-toluenesulfonic acid, the copolymer of OA and HEA P(OA-co-HEA) mainly comprises OA and HEA; the copolymer of GMA and OA P(GMA-co-OA) mainly comprises GMA and OA.
8. The polyethylene terephthalate protective film according to claim 7, characterized in that: The mass ratio of the HEA to the OA is 1:(3-10); The mass ratio of the P(OA-co-HEA) to the thioglycolic acid is 1:(0.5-1), the mass ratio of the P(OA-co-HEA) to the xylene is 1:(5-10), and the mass ratio of the p-toluenesulfonic acid to the thioglycolic acid is 1:(50-100).
9. The polyethylene terephthalate protective film according to claim 7, characterized in that: The mass ratio of the GMA to the OA is 1:(2-5).
10. The polyethylene terephthalate protective film according to claim 7, characterized in that: The mass ratio of the triethylenetetramine, the thiol-containing polymer P(OA-co-HEA)-SH and the copolymer of GMA and OA P(GMA-co-OA) is (0.1-1.5):(0.5-2):(10-100); the ratio of the total mass of triethylenetetramine, P(OA-co-HEA)-SH and P(GMA-co-OA) to ethyl acetate is 1:(2-5).
